Abordagens da multimodalidade no ensino de língua portuguesa: análise de material didático e proposta pedagógica - Araújo, Layane de Santana (2023)
Starting from the premise that multimodality is an inherent aspect of every text, as proposed by Kress and Van Leuween (1998), this work sought, in general, to carry out an analysis with the aim of verifying how the reading approach is produced multimodal from Portuguese. Collection: Idiomas (2022), by Cereja and Vianna, adopted for the last years of primary school. To theoretically support this work, we use studies by Kress and Van Lauween (1998, 2001 and 2003), Dionísio (2005, 2011 and 2016) and Ribeiro (2016, 2020) on multimodality, multimodal texts and semiotic modes; y, to carry out the analysis, it was essential to read the official documents that guide the teaching of the Portuguese language in Brazil, the National Curricular Parameters (Brazil, 1998), the Common National Curricular Base (Brazil, 2017) and the National Law Text Book Program Guide (Brazil, 2023). In methodological terms, it is a qualitative investigation of documentary analysis, based on our corpus, the collection Portuguese: Idiomas (2022), directed to the last years of the primary school, and is also characterized by being exploratory and which implies survey. bibliography on multimodality, the catalog of all texts and analysis of the multimodal reading offer and the semiotic modes present in the constitution of the texts of the collection. The results indicate that the collection presents, at various times, an unsatisfactory multimodal reading approach based on the questions proposed behind the texts and, in some activities, the semiotic modes are worked in a superficial way, thus, the volumes prepared by Cereja and Vianna (2022) does not understand, in a large part of his compositions, the guidelines of official documents to work with the multimodality of texts. As a result of these results, an interactive electronic book was produced, with the aim of allowing Portuguese language teachers to come into contact with pedagogical material that guides and expands the multimodal reading proposal based on texts from the Portuguese: Languages collection. (2022). It is also expected that this didactic proposal will fill the gaps in the volumes of the collection and allow not only the teacher, but also the students, a better understanding of the importance of semiotic modes in the constitution of texts and in multimodal reading.